2011
DOI: 10.1038/cgt.2011.13
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell-directed lentivector vaccine induces antigen-specific immune responses against murine melanoma

Abstract: Lentivectors are potential vaccine delivery vehicles because they can efficiently transduce a variety of non-dividing cells, including antigen-presenting cells, and do not cause expression of extra viral proteins. To improve safety while retaining efficiency, a dendritic cell (DC)-specific lentivector was constructed by pseudotyping the vector with an engineered viral glycoprotein derived from Sindbis virus. We assessed the level of anti-tumor immunity conferred by this engineered lentivector encoding the mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…As shown in Figure 1B, approximately 60% of the 293T.DC-SIGN cells displayed PSCA expression post-DCLV-PSCA transduction, whereas only 6.79% were PSCA-positive in the 293T cells. The specificity observed here is consistent with previous reports showing the ability of DCLV to preferentially transduce DC-SIGN-expressing cells [41], [44]. We further investigated whether DCLV-PSCA could target and mediate PSCA expression in bone marrow-derived DCs (BMDCs).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…As shown in Figure 1B, approximately 60% of the 293T.DC-SIGN cells displayed PSCA expression post-DCLV-PSCA transduction, whereas only 6.79% were PSCA-positive in the 293T cells. The specificity observed here is consistent with previous reports showing the ability of DCLV to preferentially transduce DC-SIGN-expressing cells [41], [44]. We further investigated whether DCLV-PSCA could target and mediate PSCA expression in bone marrow-derived DCs (BMDCs).…”
Section: Resultssupporting
confidence: 91%
“…injections resulted in a much lower response (<0.5%). This response trend is consistent with results from immunization with DCLV encoding HIV-1 Gag [45] or human gp100 [44]. Based on the i.d.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, other strategies include encapsulating peptides in biodegradable polymers that are phagocytized by DCs [127], preparing DCs fused with tumor cells [128], or pulsing DCs with RNA encoding tumor antigens [129]. In recent years, the use of lentiviruses to induce stable transduction of DCs has also been successfully evaluated [130132]. These vectors have the advantage of infecting nondividing cells, thus being excellent tools to express different molecules in DCs.…”
Section: Dendritic Cells and Antitumor Therapymentioning
confidence: 99%
“…Previous work in our laboratory has shown that LV pseudotyped with a modified Sindbis glycoprotein can directly target DC-SIGN on the surface of DCs [10]. This targeting was able to elicit a stronger immune response than a non-targeted vector [11]. Here, we sought to utilize LV to deliver breast cancer antigens to DCs in order to stimulate the host’s immune response against a tumor.…”
Section: Introductionmentioning
confidence: 99%